Meningkatkan Hasil Belajar Matematika Materi Perkalian melalui Pendekatan Kontekstual pada Siswa Kelas III SDK Waiara - Maria Kristina; Marianus Yufrinalis; Lukas Bera (Journal on Education, 2023)
This research is a Class Action Research (PTK) which is carried out in two cycles. The purpose of this study is to determine the application of a contextual approach in improving students' ability to calculate multiplication. The subjects of the study were grade III students of Waiara Catholic Elementary School. The data needed in this study are quantative and qualitative data consisting of learning outcomes data, observation results on learning implementation, learning outcomes assessment rubrics, and process assessment. These data are sourced from students and the school. Data analysis using quantitative and qualitative analysis. Quantitative analysis is used to explain the success rate of students in calculating on the multiplication material. While a qualititative nalisis is used to explain changes in the behavior of students and researchers in the learning process. The results showed that the use of a contextual approach to multiplication material can improve the learning outcomes of grade III semester I students at Waiara Catholic Elementary School for the 2022/2023 Academic Year. This is shown by the percentage of student completion of 76% in cycle I increased to 92% in cycle II.